Knowledge and practices of hand hygiene in health workers. Armenia 2008 – 2009 (Revista de Investigaciones Universidad del Quindío, 2010)
Objetive: describe knowledge and practices related to hand hygiene in health care workers and make suggestions for intervention with the results. Materials and methods: 99 people including physicians and nurses agreed to participate and signed informed consent; we conducted a survey of knowledge and practices and evaluated the technique of hand hygiene according to the guidelines of theWorld Health Organization. Results: Good practice was found in 27.5% of the people, fair in 38.5% and poor in 34.1%. Work experience and the type of health worker were found to be significantly related to the proper or improper performance of the technique of hand hygiene. The increased frequency of good practice was found among those who had been working for less than 6 years (60%) while it was lower among those who had been working for 21 or more years (11.1%). The participants knew the importance of hand hygiene and the benefits of using alcohol solutions. Knowledge of the information was generally good and ranged between 70 and 98%. Conclusions: It's necessary to find strategies to encourage the practice of hand hygiene and proper technique according to the guidelines of the Challenge of World Alliance of patient safety “CleanCareisSaferCare”
Keywords: hand hygiene; patient safety; knowledge about hand hygiene; hand washing; hand hygiene with alcohol solutions